Unifikasi Pendidikan Karakter Berbasis Agama Islam dalam Pendidikan Sosial di SMPN 1 Purwokerto - Tutuk Ningsih (LPPM Press, 2012)
This study aims to describe about some of the following: (1) the material of character educationbased Islam in social studies learning, (2) the pattern of implementation of character education in theSMP-1 Kedung Banteng, (3) unification of the Islamic faith-based character education in social studieslearning and (4) the effect of the implementation of character education based Islamic in social studieslearning. Methods of data collection was done by using interviews, documentation, and interviews.Methods of data analysis done with descriptive qualitative approach. Withdrawal of a conclusion basedon the results of the analysis and discussion with respect to the themes underlying problems or things thatare more substantive. Based on the discussion of the results obtained some conclusions as follows: (1)teaching materials relevant to the Islamic-based character education, and need to be taught to students,at least include a few subjects, namely: (a) the nature of man as a creature of God, (b ) devotion andrespect for parents, (c) respect for others, (d) behave in manners, (e) helping each other with each other,(f) exemplary, (g) of academic honesty and non-academic, (h) responsibility, (i) justice, (j) spirit ofpatriotism, leadership, integrity of the Unitary Republic of Indonesia, and the Pancasila, and (k) thecharacter of a religious nation, (2) the pattern of the implementation of character education in schools beintegrated between intracurricular and extracurricular activities. And the role of principal is veryimportant, (3) of Unification-based implementation of character education based of Islamic religion inthe teaching of Social Science in school SMPN-1 Kedung Banteng showed that all respondents(principals, teachers, staff, and administrators OSIS) states have a positive and highly important, andneed to be incorporated into the curriculum, and (4) Implementation Character Education based Islamicreligion in the learning process in the IPS to the character students of SMP-1 Kedung Banteng has apositive and significant influence.